ChemInform Abstract: Chemical Construction and Structural Permutation of Neurotoxic Natural Product, Antillatoxin: Importance of the Three‐Dimensional Structure of the Bulky Side Chain. Issue 29 (22nd July 2014) - Inoue, Masayuki
Abstract Review: 51 refs.